The Role of Editorial Design in University Digital Communication: A Case Study of the NotiFACSO Newsletter of the University of Guayaquil - Loor Rosales, Joffre Bernardo; Galarza Orrala, Génesis Belén; Bravo Gallardo, María Magdalena (Scripta Mundi, 2025)
Editorial design has established itself as a strategic component in university digital communication, allowing for the structuring of informative content in a clear, hierarchical, and visually coherent manner. This study analyzes the NotiFACSO digital newsletter of the Faculty of Social Communication Sciences at the University of Guayaquil, with the aim of evaluating the effectiveness of its editorial design in digital environments. The research was conducted in three phases: a visual analysis of the newsletter, an institutional survey administered to students and faculty, and an evaluation of digital metrics on social media. The results demonstrate adequate graphic organization, typographic consistency, and color segmentation, which enhance the reading experience and reinforce the institutional identity. However, opportunities for improvement were identified in accessibility, interactivity, and content personalization. The study concludes that editorial design, when applied strategically, contributes to strengthening institutional communication and the active participation of the academic community in digital environments.
Keywords: graphic design; communication; brand management; digital communication; university communication; newsletter